2005
DOI: 10.1002/hep.20582
|View full text |Cite
|
Sign up to set email alerts
|

Fractalkine and CX3CR1 are involved in the recruitment of intraepithelial lymphocytes of intrahepatic bile ducts

Abstract: Fractalkine is a chemokine with both chemoattractant and cell-adhesive functions, and in the intestine it is involved with its receptor CX3CR1 in the chemoattraction and recruitment of intraepithelial lymphocytes. We examined the pathophysiological roles of fractalkine and CX3CR1 in normal and diseased bile ducts. Expression of fractalkine and CX3CR1 were examined in liver tissues from patients with primary biliary cirrhosis (17 cases) and controls (9 cases of primary sclerosing cholangitis, 10 cases of extrah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
126
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 149 publications
(139 citation statements)
references
References 50 publications
11
126
0
1
Order By: Relevance
“…This trend confirmed the findings in our previous report [9], where serum fractalkine levels in all controls including healthy controls and patients with extrahepatic biliary obstruction and HCV-related chronic hepatitis were <3.0 ng/ml [9]. Next, the correlation between fractalkine levels and liver function data (ALT and ALP levels) and IgM levels was examined.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…This trend confirmed the findings in our previous report [9], where serum fractalkine levels in all controls including healthy controls and patients with extrahepatic biliary obstruction and HCV-related chronic hepatitis were <3.0 ng/ml [9]. Next, the correlation between fractalkine levels and liver function data (ALT and ALP levels) and IgM levels was examined.…”
Section: Resultssupporting
confidence: 89%
“…We previously reported that damaged bile ducts and vessels in PBC express fractalkine and that the induction of fractalkine expression in biliary epithelial cells is closely associated with biliary and periductal innate immunity [9,10]. In the present study, we measured serum fractalkine levels using different PBC patients' sera and obtained a similar average and distribution.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations